GhTIE1 Regulates Branching Through Modulating the Transcriptional Activity of TCPs in Cotton and Arabidopsis - Diao, Yangyang; Zhan, Jingjing; Zhao, Yanyan; Liu, Lisen; Liu, Peipei; Wei, Xi; Ding, Yanpeng; Sajjad, Muhammad; Hu, Wei; Wang, Peng; Ge, Xiaoyang (Frontiers in Plant Science, 2019)
Transcription factors (TFs) and transcriptional regulators are important switches in transcriptional networks. In recent years, the transcriptional regulator TIE1 (TCP interactor containing EAR motif protein 1) was identified as a nuclear transcriptional repressor which regulates leaf development and controls branch development. However, the function and regulatory network of GhTIE1 has not been studied in cotton. Here, we demonstrated that GhTIE1 is functionally conserved in controlling shoot branching in cotton and Arabidopsis. Overexpression of GhTIE1 in Arabidopsis leads to higher bud vigor and more branches, while silencing GhTIE1 in cotton reduced bud activity and increased branching inhibition. Yeast two-hybrid (Y2H) and bimolecular fluorescence complementation (BiFC) assays showed that GhTIE1 directly interacted with subclass II TCPs (GhBRC1, GhBRC2, and GhTCP13) in vivo and in vitro. Overexpression of GhBRC1, GhBRC2, and GhTCP13 in mutant brc1-2 partially rescued the mutant phenotype and decreased the number of branches, showing that these TCPs are functionally redundant in controlling branching. A transient dual-luciferase reporter assay indicated that GhTIE1 repressed the protein activity of GhBRC1 and GhTCP13, and thereby decreased the expression of their target gene GhHB21. Gene expression level analysis in GhTIE1 overexpressed and silenced plants also proved that GhTIE1 regulated shoot branching via repressing activity of BRC1, HB21, HB40, and HB53. Our data reveals that shoot branching can be controlled via modulation of the activity of the TIE1 and TCP proteins and provides a theoretical basis for cultivating cotton varieties with ideal plant types.